Phytochemical Screening and Proximate Analysis of Newbouldia laevis and Allium sativum - Ayoola, A.A; Yusuf, A.O; Oki, D.G (Nigerian Journal of Animal Science, 2023)
The study was conducted to assess the phytochemical and proximate composition of Newboudia laevis leaves and Allium sativum bulb extracts. The leaves and bulbs extracts were analyzed for their chemical composition and antinutritional factors (ANFs) which include moisture, crude protein, crude fat, crude fiber, total ash, carbohydrate fractions (CHO), metabolisable energy (ME),neutral detergent fiber (NDF)and phytochemicals. The phytochemical screening revealed the presence of flavonoids, terpenoids, tannin, alkaloids, phytic acid, trypsin inhibitor, phenols, antioxidants, carotenoids, oxalate and cyanide in the plant and bulb extracts.The percentages of flavonoid, terpenoid, tannin, alkaloid, phytic acid, trypsin inhibitor, phenol, antioxidants, carotenoid, oxalate and cyanide in the Newbouldia laevis were 0.15, 2.29, 392, 2.51, 2.96, 29.20, 2.86, 1.63, 624, 0.44 and 0.01mg/100g respectively, while that of the Allium sativum were 0.04, 0.07, 7.0, 4.59, 27.80, 0.25, 0.041, 0.23, 11.40, 9.02 and 0.685mg/100g, respectively. The percentage composition of moisture, crude protein, crude fat, crude fiber, ash, NFE, ME and NDF for Newbouldialaevis were 55%, 5.68%, 5.61%, 10.54%, 2.15%, 21.02%, 1626.80kcal/kg and 20.22%, while Allium sativum had 82%, 4.63%, 0%, 6.72%, 5.66%, 0.99%, 320.25kcal/kg and 0%, respectively.Therefore, it can be concluded that Newbouldialaevis leaves and Allium sativum bulbs contain bioactive substances beneficial to animals with antinutrient concentrations below the critical levels hence not deleterious to ruminant animals.